EFEKTIVITAS PUBLISITAS: MENILAI REPUTASI INSTITUSI - Nunung Prajarto (Jurnal Ilmu Komunikasi, 2008)
Institutional reputation is commercially significant since this closely deals with share- holder value, finance, independency and market share. Notwithstanding the fact that some in- stitutions do not consider reputation in more detail, others pay highly attention on it. This leads to the needs for measuring and evaluating publicity. Nonetheless, the way to define publicity effectiveness is not simply operated by some institutions. This paper introduces an alternative formula to define publicity effectiveness level mostly needed by some institutions, including business and academic institutions.